INSENSITIFITAS ASETILKOLINESTERASE (AChE) NYAMUK Aedes aegypti TERHADAP MINYAK SERAI WANGI (Cymbopogon nardus) - Khoiriyah, Yustin Nur; Sarlinda, Febrina (Poltekkes Kemenkes Tanjung Karang, 2024)
Aedes mosquitoes are vectors of viruses, namely the dengue virus. Treatment with insecticides is no longer effective if the target mosquito is resistant. Therefore, efforts are needed to overcome the resistance of these mosquitoes. Inhibition of the enzyme acetylcholinesterase (AChE) is one way the synthetic insecticide Profenofos works; if AChE is inhibited, acetylcholine accumulation will disrupt the nervous system. Insensitivity to AChE is one mechanism of mosquito resistance to insecticides. Based on this, the problem is formulated as follows: is the increase in susceptibility of Aedes aegypti mosquitoes to alphacymethrin, citronella oil, and a combination of both caused by a decrease in the insensitivity of mosquito AChE? This study aims to determine the AChE insensitivity of Aedes aegypti mosquitoes to citronella oil, a combination of citronella oil and alphacymethrin 0.03%), compared to the positive control (insecticide alphacymethrin 0.03%). Percentage of mosquito mortality after being held for 24 hours: The results showed no difference between the two groups of mosquitoes without treatment (A) and 100 µL/L citronella oil (B), F count 0.000, Sig. 1.000, significance value <0.05. Exposure to 100 µL/L citronella oil on instar III-IV mosquito larvae did not make mosquitoes more susceptible or more resistant to 0.03% alphacypermethrin insecticide. Based on the absorption value analysis results using the T-test between group A/ without treatment and group B with 100µL/L citronella oil treatment showed a Sig. (2-tailed) value of 0.547>0.05 means there is no significant difference between the two groups.